Optical coherence tomography angiography findings in patients affected by giant cell arteritis, with and without ocular involvement: a pilot study - Vannozzi, Lorenzo; Nicolosi, Cristina; Vicini, Giulio; Bacherini, Daniela; Giattini, Dario; Urban, Maria Letizia; Palermo, Adalgisa; Malandrino, Danilo; Bello, Federica; Virgili, Gianni; Giansanti, Fabrizio (Frontiers in Medicine, 2024)
Purpose: We evaluated the clinical features and retinal and disc perfusion characteristics, by using OCT and OCTA in a subset of giant cell arteritis (GCA) patients who manifested anterior ischemic optic neuropathy (AION), in a subset of GCA patients without ocular involvement, and in a control group composed by healthy controls. Methods: We performed an observational study on eyes of GCA patients affected by arteritic AION both in acute and chronic phase, unaffected eyes of AION, eyes of GCA patients without ocular involvement, and a control group of healthy eyes of healthy individuals. All patients underwent a complete ophthalmic examination, and OCT and OCTA of the macula and the disc. Results: The study evaluated 10 eyes of GCA patients with AION (AION group), 8 unaffected eyes of GCA patients with AION in other eye (unaffected eyes of AION group), 16 eyes of GCA patients without ocular involvement (non-ocular group) and 22 eyes of healthy patients (healthy group). The Ganglion Cell Complex superior and inferior thicknesses were significantly lower in the AION group compared to the unaffected eyes of AION group. All OCTA vascular density parameters of the optic disc analyzed in this study (Optic Nerve Head (ONH) whole, superior, inferior, radial peripapillary capillary plexus whole, superior, inferior, Lamina Cribrosa whole, superior, inferior) resulted significantly lower in the AION group compared to unaffected eyes group. The ONH whole and inferior were statistically higher in the healthy group in comparison to the group of GCA patients without ocular involvement. The ONH inferior was also statistically higher in the unaffected eyes of AION group, in comparison to the non-ocular group. Regarding the OCTA macular vessel density parameters, the superficial capillary plexus whole and inner were statistically lower in the AION group compared with the unaffected eyes of AION group. Conclusion: We found a profound vascular impairment in eyes affected by AION and areas of hypoperfusion 3 in eyes of patients with GCA without ocular involvement, that had good BCVA, and were clinically unremarkable. We hypothesized that these areas of lower vessel density might represent areas of subclinical hypoperfusion, that cannot be appreciated ophthalmoscopically.